2022
DOI: 10.1111/jfb.15224
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting riverine distribution and habitat use of the Japanese eel, Anguilla japonica, and the giant mottled eel, Anguilla marmorata, in a sympatric river

Abstract: Electrofishing and visual observations revealed contrasting riverine distribution and habitat use of the Japanese eel, Anguilla japonica, and the giant mottled eel, Anguilla marmorata, in a relatively gentle-slope river of Southern Kyushu, Japan. A. japonica was distributed in the lower and upper reaches. A. marmorata inhabited the middle reaches with relatively fast water velocity, heterogeneous water depth, coarse substrata and no adjacent paddy fields. This may have important conservation implications becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…For giant mottled eels, smaller rivers and higher elevations yielded higher eDNA concentrations (Table 1 and S3). This is consistent with the report by Matsushige et al (2022) that giant mottled eels are found in midstream areas. Better results could be achieved by improving eDNA sampling methods, such as sampling multiple sites at the same location.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…For giant mottled eels, smaller rivers and higher elevations yielded higher eDNA concentrations (Table 1 and S3). This is consistent with the report by Matsushige et al (2022) that giant mottled eels are found in midstream areas. Better results could be achieved by improving eDNA sampling methods, such as sampling multiple sites at the same location.…”
Section: Discussionsupporting
confidence: 94%
“…Giant mottled eels are reported to inhabit upstream areas where springs are present, while Japanese eels are commonly found downstream (Williamson et al, 1993;Ishibashi et al, 2001). Recent studies reported that giant mottled eels are found in midstream areas that are not adjacent to rice paddies, whereas Japanese eels are dominant in more downstream areas (Matsushige et al, 2022). Shiao et al (2003) also found that giant mottled eels preferred deep pools in the river, and speculated that both interspecific competition and adaptive radiation occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the 5-55 cm TL individuals of both species, the extent of overlap in habitat use was relatively limited because A. marmorata used more lotic habitats with larger substrates compared with A. japonica. These results are consistent with previous studies(Kumai, Kuroki & Morita, 2021;Matsushige, Yasutake & Mochioka, 2022), considering that the individuals in this TL range were dominant for both species. However, the GAMMs showed that there was still partial overlap in these two parameters in the habitats mainly used by the two species in this TL range, indicating the presence of interspecific competition.…”
supporting
confidence: 93%
“…These two species co‐occur in rivers in the transitional zone between temperate and subtropical East Asia, where they exhibit contrasting habitat use at a mesohabitat scale (e.g. riffles, runs and pools) in terms of current velocity and substrate size in rivers where they coexist (Kumai, Kuroki & Morita, 2021; Matsushige, Yasutake & Mochioka, 2022). However, ontogenetic habitat shifts have not been sufficiently considered in studies conducted in rivers both where they coexist and where they do not coexist (Itakura & Wakiya, 2020; Kume et al, 2020; Matsushige, Yasutake & Mochioka, 2020), possibly leading to the misevaluation of habitat use and segregation patterns.…”
Section: Introductionmentioning
confidence: 99%